Nietzsche and Adorno on philosophical praxis, language, and reconciliation towards an ethics of thinking - Bolaños, Paolo A. (Contemporary studies in idealism., 2020)
"This book experiments with Nietzsche and Adorno who are contemporary proponents of early German Romanticism. By reconstructing the philosophies of language of these thinkers, and their critique of metaphysics and identity thinking, this book develops a notion of philosophical praxis that is grounded in the ethical dimension of thinking"--